Current management of children and young people with heterozygous familial hypercholesterolaemia - HEART UK statement of care. (November 2019) - Ramaswami, Uma; Humphries, Steve E.; Priestley-Barnham, Lorraine; Green, Peter; Wald, David S.; Capps, Nigel; Anderson, Mark; Dale, Peter; Morris, Andrew A.
Abstract: This consensus statement on the management of children and young people with heterozygous familial hypercholesterolaemia (FH) addresses management of paediatric FH in the UK, identified by cascade testing when a parent is diagnosed with FH and for those diagnosed following incidental lipid tests. Lifestyle and dietary advice appropriate for children with FH; suggested low density lipoprotein cholesterol (LDL-C) targets and the most appropriate lipid-lowering therapies to achieve these are discussed in this statement of care. Based on the population prevalence of FH as 1/250 and the UK paediatric population, there are approximately 50, 000 FH children under 18 years. Currently only about 550 of these children and young people have been identified and are under paediatric care. Highlights: Children with heterozygous familial hypercholesterolaemia (FH) should be managed by paediatric health professionals with expertise in FH. Statin to be considered by the age of 10 years and use age appropriate target LDL-C level in children with FH. Dietary and life style advice should begin in early childhood. From the age of 14 years, consider joint review with adult lipidologist in transition clinic with transfer to adult lipid clinic at 16 to 18 years.